Histomorphometric Findings on the Neocerebellar Purkinje Cells and Layer V Cerebral Pyramidal Cells Following Monosodium Glutamate Exposures. (Journal of Basic and Applied Research in Biomedicine, 2022)
This study assessed some effects of monosodium glutamate which is one of  the most abundant naturally occurring amino-acids that is frequently used as a seasoning material on   histomorphometry on neocerebellar Purkinje and layer V neocerebral motor pyramidal cells in adult Wistar rats. MATERIALS AND METHODS: Forty-eight adult male Wistar rats weighing between 70-130g (8-10 weeks old) were randomly separated into four groups, each containing twelve rats. The rats in group A were regarded as the controls and they received only distilled water during the treatment period. The Wistar rats in group B, C and D received respectively 2g/kg, 4/kg and 6g/kg body weight of MSG orally once duty for 28 consecutive days. The rats were euthanized on 29th day and the whole brain and cerebellum were carefully excised, weighed   and immediately fixed in 10% buffered formal saline for histological procedures for evaluation by light microscopy. RESULTS:  The results of the total brain and cerebellar weights did not show any significant difference (P > 0.05) between the MSG – treated and control rats. However, there were significant differences (P < 0.05) in the relative total brain and relative cerebellar weights between the MSG – treated and control rats. Morphometric findings showed significant differences in the transverse diameters of neocerebellar Purkinje and layer V neocerebral pyramidal cells between the MSG – treated and control rats. The transverse diameters of Purkinje and pyramidal cells were significantly reduced (P